Experimental modelling of apokamp discharge formation under outer electric field. (March 2020) - Kuznetsov, V S; Panarin, V A; Skakun, V S; Sosnin, E A; Tarasenko, V F
Abstract: A laboratory setup has been created for modeling certain aspects of the initiation process of blue jets in the Earth's atmosphere. With its help, the influence of an electric field on the apokamp discharge in air at pressures of 180-260 Torr was established. It is shown that the formation of a negatively charged zone located above the channel of a pulse-periodic discharge with a positive potential leads to both initiation and lengthening of the apokamps starting from the channel, and also reduces the voltage amplitude necessary for their formation.